Exploring Hadith: The Importance of Developing a Personal Brand in the Business World.: Kajian Hadits: Pentingnya Mengembangkan Personal Brand dalam Dunia Bisnis. - Dewi Chan, Sukma Sari (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2024)
What is the key to the success of the Prophet Muhammad's business? The Prophet Muhammad is known by the title al-amin among the Arab community, this is because of the honest and trustworthy attitude that he applied in the business activities he carried out. Without realizing it, the application of honesty and trustworthiness by the Prophet Muhammad SAW was his branding in business. This is what the researchers focus on in this article, revealing how the Prophet Muhammad built personal branding in business activities as stated in the hadith.